Faktor-faktor yang mempengaruhi motivasi kerja karyawan pada PT Agrita Sari Prima Di Kecamatan Langgam Kabupaten Pelalawan - Hendrayani, Hendrayani (Sekolah Tinggi Ilmu Ekonomi Riau, 2016)
The study was conducted at PT Agrita Sari Prima In District Langgam Pelalawan. Based on the research background mentioned above, the writer can formulate the problem in this study is whether the factors that influence employee motivation at PT Agrita Sari Prima In District Langgam Pelalawan. The purpose of this research was to determine the factors that influence employee motivation in PT Agrita Sari Prima.The data analysis in this research by using descriptive and quantitative methods. Methods descriptive analysis of data by the decomposition of the theories contained in the bibliography, and are associated with the data obtained from the research that will be collected, classified and tabulated then be concluded. And quantitative methods with multiple linear regression techniques. Samples taken in this study is numbered 75 (people) of the respondents, the research results are seen from the calculation F_hitung obtained a value of 84 809 and F_tabel at 2:35. with significance of 0.000 <0.05. With significant value below 0.05 indicates that in together variable Compensation, Employment Security, Choice, Working Conditions, and the leadership has a positive and significant influence on employee motivation and the coefficient of determination (Adjusted R2) obtained at 0.850. This means that 85% of work motivation is influenced by the Compensation, Employment Security, Choice, conditions of work, and leadership, while the remaining 15% work motivation is influenced by other variables not examined in this study